Waste Reduction Performance by Black Soldier Fly Larvae (Bsfl) on Domestic Waste and Solid Decanter - Rohmanna, Novianti Adi; Maharani, Dessy Maulidya (Biotropika: Journal of Tropical Biology, 2022)
Organic waste was the potential to contaminate the environment. Hermetia illucens or BSFL were the insects that could decompose waste and produce larvae biomass. It had high efficiency for waste reduction. The kind of substrate could affect the waste reduction performance of BSFL. This study determined the effect of the kind of waste on the effectiveness of reducing waste by Hermetia illucens. The larvae were reared on domestic waste and solid decanter. Each treatment (three replicates per treatment) contained 300 larvae seven days old with a daily food rate of 125 mg/larva/day. After instar fourth and fifth old, the larva was harvested using sterile forceps.Â The ratio of waste reduction (%WR), Efficiency of conversion of digested feedÂ (ECD), bioconversion rate (BCR), and biomass were calculated in the fourth and fifth instar. The results showed that larvae on domestic waste had a higher waste reduction performance than larvae on the solid decanter. The results showed that larvae could reduce domestic waste to 76.5% and 32.6% on the solid decanter. Larva on domestic wasted showed higher ECD, BCR, and biomass than larvae on the solid decanter. It showed that BSFL had higher waste reduction performance on the domestic waste than on solid decanter. Therefore the kind of waste could affect the waste reduction performance of BSF larvae.